'Winning While Losing': Borneo Headquarters and the End of Confrontation, June–November 1966. (January 2017) - Tuck, Christopher
From 1963 to 1966 Britain fought an undeclared war against Indonesia in the jungles of Borneo. Existing accounts of the tactical outcomes of this campaign take at face value the comments produced after the event by such key individuals as Sir Walter Walker, until March 1965 the British Director of Borneo Operations, who regarded the campaign as 'a complete success'. This article demonstrates that this narrative is a retrospective judgement and that senior British officers at the time regarded the conclusion of the campaign as a success for Indonesia.